2012
DOI: 10.1186/1471-2164-13-s7-s4
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing and identification of Morganella morganii KT pathogenicity-related genes

Abstract: BackgroundThe opportunistic enterobacterium, Morganella morganii, which can cause bacteraemia, is the ninth most prevalent cause of clinical infections in patients at Changhua Christian Hospital, Taiwan. The KT strain of M. morganii was isolated during postoperative care of a cancer patient with a gallbladder stone who developed sepsis caused by bacteraemia. M. morganii is sometimes encountered in nosocomial settings and has been causally linked to catheter-associated bacteriuria, complex infections of the uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 100 publications
6
68
1
1
Order By: Relevance
“…Notably, MrpJ paralogs are not restricted to P. mirabilis as they have been detected in fimbrial operons from related genera (264266). Because fimbriae allow bacteria to adhere or form biofilms in specific environments, and thus respond to niche-specific signals, MrpJ paralogs have been proposed to orchestrate genetic programs that are beneficial to those environments (132, 267).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Notably, MrpJ paralogs are not restricted to P. mirabilis as they have been detected in fimbrial operons from related genera (264266). Because fimbriae allow bacteria to adhere or form biofilms in specific environments, and thus respond to niche-specific signals, MrpJ paralogs have been proposed to orchestrate genetic programs that are beneficial to those environments (132, 267).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Searches of the recently annotated urinary pathogen Providencia stuartii 25827 genome, available in GenBank, revealed that mrpJ paralogs are also frequently associated with fimbrial operons in that species. Likewise, thirteen mrpJ paralogs are encoded by Morganella morganii , although only two are associated with fimbrial operons (206). Thus far, mrpJ paralogs have been identified by BLAST homology searches (207) in at least 20 other bacterial species.…”
Section: Mrpj Regulates the Transition Between Swimming And Swarmingmentioning
confidence: 99%
“…At the same time in which the foam exerted its analgesic effect in the lesion, it helped in the control of the infection through the absorption of the exudate by capillarity and its retention in the air spaces of the structure (20) . We can conclude that the conduct adopted, considering the presence of infection in the wound, were appropriate, once it is a immunosuppressed patient, affected by an infection by enterobacteria about which the literature demonstrates high mortality rates (26) . The same way, we may observe the effectiveness of the polyurethane foam with sustained release of ibuprofen helping in the control of the pain, since in only five days of use, there was an important reduction of the score (from 10 to 5) considering that the pain was reported only during the handling for changing the dressings.…”
Section: Discussionmentioning
confidence: 92%
“…When present, it releases toxins and enzymes, activates matrices of metalloproteinases (MMPs) and plasminogen, degrading elastin and thus interfering negatively in the healing process of the wound (24,25) . Most patients affected by M. morganii respond well to the antimicrobial treatment; however, mortality rates are high (26) . In this case, the infection was controlled with systemic antimicrobial associated to the topical, recommended in the presence of signs of systemic infection.…”
Section: Discussionmentioning
confidence: 99%